(untitled) (Bangladesh Critical Care Journal, 2019)
A 50 year old bangladeshi female, came to our emergency with hematemasis ,jaundice and abdominal pain who had a history of laparoscopic cholecystectomy 1 month ago. Patient was diagnosed as acute pancreatitis and obstructive jaundice caused by postcholecystectomic hemobilia. She also had a vascular abnormaly (Her left lobe of liver is supplied by hepatic artery and right love of liver is supplied by accessory hepatic artery which is a branch of superior mesenteric artery, and a sacular aneurysm developed in accessory hepatic artery near the gall bladder fossa (near postcholecystectomy clipping). We are reporting another case of acute pancreatitis after laparoscopic cholecystectomy caused by hemobilia secondary to pseudoaneurysm in accessory hepatic artery originating from superior mesenteric artery. This is probably second such reported case. Bangladesh Crit Care J March 2019; 7(1): 55-57